Family-Focused Public Health: Supporting Homes and Families in Policy and Practice - Hanson, Carl L.; Crandall, Ali; Barnes, Michael D.; Magnusson, Brianna; Novilla, M. Lelinneth B.; King, Jaron (Frontiers in Public Health, 2019)
Life expectancy in the US is on the decline. Mental health issues associated with opioid abuse and suicide have been implicated for this decline necessitating new approaches and procedures. While Public Health 3.0 provides a call to action for stakeholders to work closely together to address such complex problems as these, less attention has been given to engaging and supporting the most important stakeholders and primary producers of health within the US: families and households. The idea that health begins at home is discussed from the perspective of primary, secondary, and tertiary prevention levels. Primary prevention where research provides evidence for the role of the family in healthy child development. Secondary and tertiary prevention where research offers evidence for the role of the family in caregiving. Despite this evidence, greater focus and attention must be placed on the family at all prevention levels as an often overlooked setting of public health practice and level of influence. Prevention across all levels is enhanced as public health practitioners think family when designing and implementing public health policy. Four family impact principles are presented to help guide planning and implementation decisions to nourish family engagement.